Simester and Sullivan's Criminal law theory and doctrine - Simester, A. P.; Spencer, John R.; Stark, Findlay; Sullivan, G. R.; Virgo, Graham (Hart Publishing, 2016)
Simester and Sullivan's Criminal Law is an outstanding account of modern English criminal law, combining detailed exposition and analysis of the law with a careful exploration of its theoretical underpinnings. The sixth edition is comprehensively updated throughout to set out and analyse all key development in the field with the work's trademark clarity and critical rigour.